PROPERTIES OF TAWN AND TAN/TAWN COATING FILM DEPOSITED ON WC-CO-BASED CEMENTED CARBIDE USING MAGNETRON SPUTTER ION PLATING - Wada, Tadahiro (MATTER: International Journal of Science and Technology, 2018)
Titanium based coating films are generally used as the coating film. In this study, the thickness, hardness and scratch strength of TaWN and TaN/TaWN coated tools were measured. The substrate used was a cemented carbide ISO K10. The work piece used was a hardened steel AISI D2. This work piece was turned with the TaWN and the TaN/TaWN coated tools. The tool wear of the TaWN and TaN/TaWN coated tools was investigated. Furthermore, the TaN coated tool was also used. (1) Droplets on the surface of both the TaWN and TaN/TaWN coating films were negligible. (2) The hardness of the TaWN and TaN/TaWN was 2340 HV0.25N and 2630 HV0.25N, respectively. (3) The critical load of both the TaWN and TaN/TaWN coated tools was over 130 N. (4) The friction coefficient of the TaN/TaWN and TaN was 0.44 and 0.53, respectively. (5) The wear rate of the TaN/TaWN coated tool was slower than that of the TaN or TaWN coated tool.